The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.07.06.499032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A phylogenomically informed five-order system for the closest relatives of land plants

Abstract: The evolution of streptophytes had a profound impact on life on Earth. They brought forth those photosynthetic eukaryotes that today dominate the macroscopic flora: the land plants (Embryophyta) [1]. There is convincing evidence that the unicellular/filamentous Zygnematophyceae--and not the morphologically more elaborate Coleochaetophyceae or Charophyceae--are the closest algal relatives of land plants [2, 3, 4, 5, 6]. Despite the species richness (>4,000), wide distribution, and key evolutionary position o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Overall, Mesotaenium responds to stress conditions by formation of LDs containing signature proteins for embryophytic LDs. DISCUSSION Owing to their plain morphology, Zygnematophyceae emerged as unexpected closest algal relatives of land plants (Wickett et al, 2014;One Thousand Plant Transcriptomes Initiative, 2019;Hess et al, 2022). That said, the molecular programs of Zygnematophyceae speak of their close relationships to land plants.…”
Section: Lipid Droplet Formation Constitutes a Stress Response Predat...mentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, Mesotaenium responds to stress conditions by formation of LDs containing signature proteins for embryophytic LDs. DISCUSSION Owing to their plain morphology, Zygnematophyceae emerged as unexpected closest algal relatives of land plants (Wickett et al, 2014;One Thousand Plant Transcriptomes Initiative, 2019;Hess et al, 2022). That said, the molecular programs of Zygnematophyceae speak of their close relationships to land plants.…”
Section: Lipid Droplet Formation Constitutes a Stress Response Predat...mentioning
confidence: 99%
“…These data brought a surprise: the filamentous and unicellular Zygnematophyceae—and not other morphologically more elaborate algae—are the closest algal relatives of land plants. Now the first three genomes of major orders of Zygnematophyceae (see Hess et al, 2022) are at hand: Mesotaenium endlicherianum, Spirogloea muscicola (Cheng et al, 2019), and Penium margaritaceum (Jiao et al, 2020). Using these, we are beginning to redefine the molecular chassis shared by land plants and their closest algal relatives.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study suggests that such cell size variation may be partly due to genome size variation in this species. The correlation between genome size and cell size was also Micrasterias that to the same family Desmidiaceae as Closterium (Hess et al, 2022;Poulíèková et al, 2014).…”
Section: Comparison Of Genome Size and Morphological Featuresmentioning
confidence: 83%
“…Figure 1 provides an introduction to each group, and detailed information about charophyte body plans, development, reproduction, and ecology may be obtained in Graham et al (2016) . It is now thought that all land plants evolved from a single streptophyte algal progenitor 500–600+ million years ago ( Fürst-Jansen et al, 2021 ), and phylogenomic analyses have now clearly confirmed that the Zygnematophyceae are sister to embryophytes ( Delwiche and Cooper, 2015 ; Harholt et al, 2016 ; de Vries and Archibald, 2018 ; Puttick et al, 2018 ; Zhou and von Schwartzenberg, 2020 ; Hess et al, 2022 ).…”
Section: The Charophytes Groupsmentioning
confidence: 99%